Socio-Cultural Adaptation in Japan: How Malaysian International Students Deal with Challenges? - Nor, Rahimah Muhammad; Mustafa, Zakaria (EDUCARE, 2013)
ABSTRACT: International-level migration among young people is an effective way for students to be exposed to cultural diversity in order to develop global awareness, personal competence, intercultural skills, and prospective careers for the future. In addition, an individual with intercultural skills has an advantage in effective teamwork or collaboration with others in a multi-cultural workplace. The purpose of this article is to determine differences in level of four learning outcomes on the impacts of socio-cultural adaptation in Japan from the Malaysian international studentsâ perspectives (N=245). Using the statistical method of Friedman test, analysis revealed significant differences in level of learning outcomes [Ï2 (3, N = 245) = 480.173, p < .05] with mean ranks of personal competence (2.27); intercultural competence (3.99); global competence (2.07); and skills competence (1.67). In addition, qualitative analysis through narrative method demonstrated that the struggles of adaptation issue significantly influence impacts on studentsâ learning and development: independence, self-confidence, expanding world-view, psychological adjustment, understanding of cultural differences, self-cultural awareness, objectivity in making decision, and problem-solving skills. Individuals living abroad deal with various challenges and difficulties situations, such as new physical environment, difference in customary practices, difference in way of thinking, language barrier, cultural shock, lack of emotional support, and difficulty in maintaining own values and beliefs. The researchers believe that for a successful socio-cultural adaptation, individuals need to express their willingness to learn and accept other cultures through psychological, behaviour, and cognitive changes. KEY WORDS: Personal competence, intercultural competence, global competence, skills competence, socio-cultural in Japan, and Malaysian international students.Â Â About the Authors: Rahimah Muhammad Nor is a Graduate Student (M.A.) at the Department of East Asian Studies, Faculty of Arts and Social Sciences UM (University of Malaya), 50603 Kuala Lumpur, Malaysia; and Zakaria Mustafa is a Lecturer at the Department of East Asian Studies @ SKET, Faculty of Arts and Social Sciences UM (University of Malaya), 50603 Kuala Lumpur, Malaysia. The authors can be contacted via e-mails address at: mres2020@siswa.um.edu.my and zmusftafa@um.edu.myHow to cite this article? Nor, Rahimah Muhammad & Zakaria Mustafa. (2013). âSocio-Cultural Adaptation in Japan: How Malaysian International Students Deal with Challenges?â in EDUCARE: International Journal for Educational Studies, Vol.6(1) August, pp.91-102. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 21, 2013); Revised (July 24, 2013); and Published (August 17, 2013).Â Â